Sustainability analysis of CO2 capture and utilization processes using a computer-aided tool. (July 2018) - Roh, Kosan; Lim, Hyungmuk; Chung, Wonseok; Oh, Jaewoo; Yoo, Haeun; Al-Hunaidy, Ali S.; Imran, Hasan; Lee, Jay H.
Highlights: ArKa-TAC 3, a computer-aided analysis tool tailored to CCU processes is developed. Multiple CCU paths can be handled by adopting superstructure model framework. Techno-economic and CO2 reduction metrics of CCU processes cab be calculated simultaneously. Implementation of a CO2 -based acetic acid plant in four different countries is examined. Abstract: CO2 capture and utilization technologies (CCU) are recently attracting attention as ways to reduce CO2 emission and generate economic benefits at the same time. Since numerous potential products from CO2 may be considered and multiple processing pathways are possible for each product, there is a growing demand for a tool that can aid in techno-economic and life cycle CO2 analyses of a large number of CCU options, in order to identify promising ones. This work introduces a computer-aided analysis tool called ArKa-TAC 3 tailored for this purpose. ArKa-TAC 3 can calculate both techno-economic and CO2 reduction metrics of CCU processes in a fast and convenient manner. Sufficient flexibility is assured by adopting a superstructure model framework, which allows the user to conveniently describe a CCU processing network composed of multiple processing steps with a large number of technical options. To demonstrate the tool, a CCU process of acetic acid production is designed and its sustainability is analyzed by using it. By implementing the designed process in four different countries, it is verified that the CCU process can be made sustainable by adopting the process substitution strategies its implementation. Some perspectives on potential applications of the developed tool are given.